Software Piracy: A Literature Study on Ethical Issues in Information Technology - Muhammad Idzha Adhitya Ranius (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
Ethics constitute a set of principles, norms, and moral guidelines that direct human conduct. These ethical foundations play a vital role in technology, particularly software, which continues to evolve rapidly. The increasing demand for high-quality software has, however, encouraged unethical behavior such as software piracy. This study examines software piracy from an ethical perspective within information systems. A narrative literature review method was employed, synthesizing reputable national and international publications and established institutional practices especially scholarly journals recognized for upholding research ethics. The review identifies the major impacts, applicable legal frameworks, and potential solutions concerning the use of pirated software within Information Technology Ethics. The findings emphasize the importance of ethical awareness and the adoption of licensed software to mitigate piracy and enhance responsible technology use.